The bilateral movement condition facilitates maximal but not submaximal paretic-limb grip force in people with post-stroke hemiparesis - DeJong, Stacey L. (2012)
OBJECTIVES: Although healthy individuals have less force production capacity during bilateral muscle contractions compared to unilateral efforts, emerging evidence suggests that certain aspects of paretic upper limb task performance after stroke may be enhanced by moving bilaterally instead of unilaterally. We investigated whether the bilateral movement condition affects grip force differently on the paretic side of people with post-stroke hemiparesis, compared to their non-paretic side and both sides of healthy young adults. METHODS: Within a single session, we compared: 1) maximal grip force during unilateral vs. bilateral contractions on each side, and 2) force contributed by each side during a 30% submaximal bilateral contraction. RESULTS: Healthy controls produced less grip force in the bilateral condition, regardless of side (- 2.4% difference), and similar findings were observed on the non-paretic side of people with hemiparesis (- 4.5% difference). On the paretic side, however, maximal grip force was increased by the bilateral condition in most participants (+11.3% difference, on average). During submaximal bilateral contractions in each group, the two sides each contributed the same percentage of unilateral maximal force. CONCLUSIONS: The bilateral condition facilitates paretic limb grip force at maximal, but not submaximal levels. SIGNIFICANCE: In some people with post-stroke hemiparesis, the paretic limb may benefit from bilateral training with high force requirements.